Extensive natural variation in bacterial ribosomal drug-binding sites - Chinenye L. Ekemezie; Lewis I. Chan; Charlotte R. Brown; Karla Helena-Bueno; Tom A. Williams; Sergey V. Melnikov (Cell Reports)
Summary: Ribosomes from certain bacteria possess divergent drug-binding sites compared to those of Escherichia coli, leading to natural evasion or hypersensitivity to antibiotics. However, in the absence of systematic studies, it is unknown whether this divergence is rare or common among bacterial species. Here, we address this by reconstructing the evolutionary history of drug-binding residues in bacterial ribosomes. We find that many rRNA residues that are currently viewed as bacterial-specific features of ribosomal drug-binding sites are in fact conserved only in a subset of bacteria. Conversely, species with divergent drug-binding sites are widespread in nature, arising from ancient rRNA polymorphisms at the direct ribosome-drug interface. Using a few bacterial species harboring divergent drug-binding sites, we identify their intrinsic resistance to corresponding ribosome-targeting antibiotics. Overall, we reveal the extensive lineage-specific diversity of ribosomal drug-binding sites, offering a resource for developing more targeted antibiotics and enabling personalized drug selection for specific pathogens.